Effects of external debt capacity on infrastructure investment in the SADC region - Matla, Lindokuhle P. (University of the Witswatersrand, Johannesburg, 2023)
This report examines the effects of external public debt on infrastructure investment in the Southern African Development Community (SADC) region, and particularly assesses member countries’ borrowing capacity against the SADC Convergence Target. A multiple regression analysis is conducted on a panel data of 2004-2019 to examine the cross-country dynamics of the 16 SADC countries. The surprising research findings indicate an insignificant relationship between infrastructure investment and external public debt in the SADC region. Furthermore, macroeconomic variables such as Official Development Assistance, Political Stability, Gross National Savings, Gross Government Debt, and Consumer Price Index, individually have a significant and positive association with infrastructure investment. The findings of this research suggest that although government debt is theoretically expected to be an important factor in determining infrastructure investment, other factors appear to be more statistically significant in influencing infrastructure investment.
Research Report submitted in fulfilment of the requirements for the degree of Master of Management in Finance and Investment
Keywords: External debt; Infrastructure investment; SADC; UCTD; SDG-8: Decent work and economic growth